2015
DOI: 10.1088/0022-3727/48/29/295202
|View full text |Cite
|
Sign up to set email alerts
|

High power impulse sputtering of chromium: correlation between the energy distribution of chromium ions and spoke formation

Abstract: High power magnetron sputtering (HiPIMS) discharges generate ions with high kinetic energies in comparison to conventional dc magnetron sputtering. The peculiar shape of the ion energy distribution function (IEDF) is correlated to the formation of localized ionization zones (IZ) in the racetrack of a HiPIMS discharge, so called spokes. This is explained by a local maximum of the electrical potential inside these localized IZ. By using ion energy mass spectrometry, probe experiments and plasma spectroscopy the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 22 publications
0
27
1
Order By: Relevance
“…This contribution focuses on the investigation of the spoke's inner parameters using OES. The aim is to study the spokes with well-defined shapes, as they possess clearly visible borders on the probe and the camera signals as presented in [17,26,48,49]. Clear distinction of borders allows the precise determination of the position where the spoke starts and where it ends.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This contribution focuses on the investigation of the spoke's inner parameters using OES. The aim is to study the spokes with well-defined shapes, as they possess clearly visible borders on the probe and the camera signals as presented in [17,26,48,49]. Clear distinction of borders allows the precise determination of the position where the spoke starts and where it ends.…”
Section: Resultsmentioning
confidence: 99%
“…As the spokes are associated with a potential hump [28], any spokes passing over the Langmuir probe induce changes in the floating potential. This is demonstrated by periodic fluctuations observed on the floating potential corresponding to periodic passing of spokes [41,48,50].…”
Section: Data Processing and Interpretationmentioning
confidence: 90%
“…A few years ago, it was observed that the plasma is not always homogeneously distributed over the racetrack area of the target in high-power impulse magnetron sputtering (HiPIMS) discharges [1][2][3], but under certain conditions it is self-organised into ionisation zones called spokes [2,4]. Several non-perturbing diagnostic techniques have been used to investigate spokes; these include photo-multiplier tubes [3,[5][6][7][8], high-speed 2D imaging of broadband emission [1][2][3][5][6][7][8][9][10][11][12][13][14][15][16][17][18], spectrally filtered high-speed 2D imaging [19][20][21], streak cameras [21][22][23][24], laser-induced fluorescence [20] and embedded probes [13,25,26]. Furthermore, more perturbing methods such as the Langmuir probe (single as well as multiprobe) [3,[5][6][7][8], emissive probe [2], magnetic sensor probe [27] or triple probe…”
Section: Introductionmentioning
confidence: 99%
“…Hecimovic et al [63] investigated in detail the origin of the IEDF in HiPIMS and found that the high energy tail can be fitted with a Maxwell distribution, which indicates that the sputtered ions are also thermalized, though this will depend a lot on the pressure and the distance between the target and the substrate [62]. It is also common to see a distinct energy shoulder between the thermal ion population and the high energy tail [64,67,102,[104][105][106][107] and this was argued by Maszl et al [103] to be due to the presence of self-organizing ionization zones called spokes [108][109][110][111], which results to a potential hump that can accelerate ions [103,112]. An example of the IEDF of Ti + ions in a HiPIMS discharge is shown in Fig.…”
Section: Iedf In Hipimsmentioning
confidence: 99%